Comparison of clinical behavior between mucinous ovarian carcinoma with infiltrative and expansile invasion and high-grade serous ovarian carcinoma: a retrospective analysis - Taira Hada; Morikazu Miyamoto; Hiroki Ishibashi; Hiroko Matsuura; Soichiro Kakimoto; Hideki Iwahashi; Hitoshi Tsuda; Masashi Takano (BMC, 2022)
Abstract Background The aim of this study was to evaluate the clinicopathological factors and prognosis of mucinous carcinoma (MC) with infiltrative invasion, MC with expansile invasion, and high-grade serous carcinoma (HGSC). Methods Cases of MC and HGSC between 1984 and 2019 were identified. The clinicopathological factors and prognosis of MC with infiltrative invasion or expansile invasion and HGSC were retrospectively compared. Although our present study included cases in our previous studies, we extended observational period when analysis was performed. Accordingly, our study added increased cases and survival analysis was newly conducted. Results After pathological review, 27 cases of MC with infiltrative invasion, 25 cases of MC with expansile invasion, and 219 cases of HGSC were included. MC had a better prognosis in terms of progression-free survival (PFS, p < 0.01) and overall survival (OS, p < 0.01) than HGSC for all International Federation of Gynecology and Obstetrics (FIGO) stages; however, multivariate analysis did not show statistical differences in PFS and OS. There were no statistically significant differences in PFS and OS for all FIGO stages between MC with infiltrative invasion and HGSC. However, in cases with FIGO stages II to IV, MC with infiltrative invasion had worse PFS (p < 0.01) and OS (p < 0.01) than HGSC. In univariate analysis, MC with infiltrative invasion was a worse prognostic factor for PFS (hazard ratio [HR] 2.83, p < 0.01) and OS (HR 3.83, p < 0.01) than HGSC. Compared with HGSC, MC with expansile invasion had better PFS (p < 0.01) and OS (p < 0.01). Multivariate analysis demonstrated that MC with expansile invasion was a better prognostic factor for PFS (HR 0.17, p < 0.01) and OS (HR 0.18, p = 0.03) than HGSC. Conclusions Compared to the prognosis of HGSC, that of MC was different according to the invasive pattern and FIGO stage. Therefore, future study may be needed to consider this association.